FRI0010 Comparison with Radiographic Joint Damage in Patients with Rheumatoid Arthritis with the Continuation or Discontinuation of RAPID3 Remission during 1 Year. (10th June 2014) - Katayama, K.; Okubo, T.; Sato, T.; Kamiya, K.; Fukai, R.
Abstract : Background: RAPID3 (routine assessment of patient index-3) includes the three patient reported outcome measures: pain, global estimate for rheumatoid arthritis (RA), and physical function. Several reports have indicated the relationship between inhibition of radiographic joint damages (RJD) and the continuation of clinical remission. For example, disease activity score with 28 joint counts (DAS28) (1) which consists of joint and blood examination. However, little is known about whether the continuation of RAPID3 remission (which consists of patient oriented measures) is effective for the inhibition of radiographic joint damages (RJD) progression. Objectives: To compared inhibitory effect of RJD in RA patients with or without continuation of RAPID3 remission during 1 year. Methods: RJD were analyzed by using modified total sharp scoring method (mTSS) in hands and feet X-ray films of RA patients with RAPID3 remission at baseline and 1 year later. Results: RAPID3 remissions were observed in 285 (22.6%) patients out of 1262 RA patients at cross-sectional study from last year. 189 (66.3%) and 102 (35.7%) of patients satisfying RAPID3 remission also achieved DAS28-ESR and CDAI remission, respectively. From 285 patients, it was impossible to analyze X-ray film of 48 patients due to discontinuation of therapy or no baseline film. One hundred and five patients from 237 patients were not yet available for this study right now due to shortage of observation. Finally, 132 patients were available for this study. Eighty-nine patients (67.4%) achieved the continuation of RAPID3 remission during 1 year. Forty-two patients (32.6%) failed to the continuation of RAPID3 remission during 1 year. Mean baseline clinical data of patients with or without continuation of RAPID3 remission were as follows: age; 59.1 and 63.7 years (p<0.05), duration of RA; 5.4 and 8.0 years (p<0.05), DAS28-ESR; 2.15 and 2.73 (p<0.05), tender joint counts, 0.81 and 1.87 (p<0.05), swollen joint counts, 1.89 and 2.81 (p<0.05). There were no significant differences in RF, anti-CCP antibody and MMP3 between two groups. RAPID3 at 1year changed to 1.08 in the continuation group (p=0.18) and increased to 7.17 in the discontinuation group (p<0.001). There were also significant differences between the RAPID3 values at 1 year (p<0.001). DAS28-ESR and Health Assessment Questionnaire Disability Index (HAQ- DI) did not changed in the continuation group (from 2.15 to 2.06 and from 0.06 to 0.05, respectively). On the other hand, DAS28-ESR and HAQ-DI changed in the discontinuation group (from 2.73 to 3.39 and from 0.14 to 0.29, respectively). ΔDAS-ESR and ΔHAQ-DI were significantly increased in the discontinuation group compared with those in the continuation group (p<0.001). The ΔmTSS/year and structural remission rate was 0.17 and 83.1% in the continuation group, 0.41 and 71.4% in the discontinuation group, although significant differences were not observed. Conclusions: The improvement of DAS28 and HAQ-DI in RA patients with continuation of RAPID3 remission during 1 year were more effective compared with those with discontinuation of RAPID3 remission. However inhibition of RJD were not significantly different between two groups. References: Aletaha D and Smolen JS (2011) Arthritis rheum, 2011; 63:3702-3711 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2000